Hubungan Antara Kontrol Diri Dengan Celebrity Worship Pada Remaja Penggemar K-pop - Abdilah, Sekar Viqi; Muzzamil, Ferdy (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to determine the relationship between self-control and celebrity worship in adolescent K-Pop fans. This type of research is quantitative with a correlation approach. This study uses adolescent K-Pop fans as research respondents. The sampling technique in this study was by using non-probability sampling and using the purposive sampling method. The number of samples used as respondents in this study was 122 respondents. Based on the results of the correlation hypothesis test, a correlation score of -0.318** was obtained with a significance value of p <0.01. The results showed that there was a weak relationship between self-control and celebrity worship and there was a negative relationship between self-control and celebrity worship, which means that the lower the self-control, the higher the celebrity worship, and vice versa, the higher the self-control, the lower the celebrity worship.